How Do Service Employees Manage Violence? The Impact of Community Violence on Women’s Emotional Demand in the Public Sector of Ethiopia - Eyasu, Nahom (Journal of interpersonal violence, 2022)
The experiences of violence against women employees can lead to long-term psychosocial problems in institutions, thereby preventing them from becoming productive citizens. Although many studies have focused on the effects of violence on women’s job performance, there exist few works on the effects of community violence on women’s emotional demand in the workplace. To address this gap, this research examines the impact of community violence on emotional labor and emotional dissonance in the public sector. This study involved 67 participants (20 semi-structured interviews, 32 participants in four focus group discussions, and 15 key informants), derived using a purposive sampling technique. Data were analyzed using thematic analysis to explore participants’ explanations about the exposure and expression of community violence on women’s emotional demands. Explanations were presented in terms of exposure (the state of being exposed to community violence) and expression (the reaction of victims to exposure in the workplace). The findings showed that the exposure of community violence on emotional labor can be expressed into three classifications: Gum up, Bottle up, and Defeatists (GBD). Furthermore, the study found out that women employees tend to conceal their felt emotions mainly due to the fear of reprisal, chiding rebuttal, and lack of support. The findings of the current study have policy implications. They can inform the micro-, meso-, and macro-level intervention efforts in mitigating the impacts of community violence on women’s emotional demand at work.